The effect of lymphoid antigen expression on prognosis of the patients with acute myeloblastic leukemia - (:unkn) unknown (My University, 1997)
Objective: Lymphoid antigen expression is very common in patients with acute myeloblastic leukemia (AML), but the predictive value of lymphoid antigen expression on the prognosis of AML remains unclear. In this study we tried to find out the effect of lymphoid antigen expression on prognosis of the patients with acute myeloblastic leukemia. Methods: Seventy patients with AML, admitted to Marmara University Hospital between January 1989 and December 1995, were analyzed for blast cell lymphoid antigen expression, and prognosis. Lymphoid antigens examined on the myeloblasts were CD2, CD3, CD7, CD10 and CD19. Results: Twenty-four patients (34.2%) had one or more positive lymphoid antigens present in their blasts. Six patients had T lymphoid associated antigen (8.5%), 12 patients had B lymphoid associated antigen (17.1%) and six patients had both B and T lymphoid antigens (8.5%). No differences were found between lymphoid marker positive and negative groups in terms of age, leukocyte count on admission, serum LDH levels, complete remission rate, relapse rate and survival. Four out of six patients (67%) expressing both T and B lymphoid antigens died within the first month of the diagnosis. The early mortality rate of this group was different from the patients whose blasts expressed T or B lymphoid antigens alone (67% v 11% p < 0.02), and was higher than that was seen in the lymphoid antigen negative group although not statistically different (67% v 32% p:0.1). Conclusion: Although the number of patients was limited, T and B lymphoid antigen coexpression on AML blasts may be a predictor of poor outcome and this needs to be further investigated in a large scale of clinical trial.
Keywords: Acute myeloblastic leukemia; B lymphocyte associated antigens; Lymphoid associated antigens; T lymphocyte associated antigens